Risk factors for ischemic osteonecrosis of the femoral head after internal fixation with multiple cannulated screws for Pauwels type III femoral neck fracture - Yang, Shuo (Vojnosanitetski pregled, 2024)
Background/Aim. Numerous factors lead to hip fractures that are common and often devastating in the geriatric population. The aim of the study was to determine the risk factors for ischemic osteonecrosis of the femoral head (ONFH) in patients after internal fixation with multiple cannulated screws for Pauwels type III femoral neck fracture (FNF). Methods. A total of 212 patients with Pauwels type III FNF, who underwent internal fixation with multiple cannulated screws from January 2019 to September 2022 and received one-year follow-up after surgery, were selected. Based on their clinical data and the incidence of ONFH, they were divided into two groups: the group with ischemic ONFH occurrence (n = 30) and the ischemic ONFH non-occurrence group (n = 182). Logistic regression analysis was conducted to analyze the risk factors for postoperative ischemic ONFH. Results. Age, body mass index (BMI), time from injury to surgery, partial weight bearing (PWB) time after surgery, and preoperative diabetes mellitus (DM) were significantly different between the ischemic ONFH occurrence and ischemic ONFH non-occurrence groups (p < 0.05), while other clinical data showed no significant differences (p > 0.05). The results of logistic regression analysis revealed that age (> 55 years), PWB time after surgery (≤ 3 months), BMI (≥ 24 kg/m2), time from injury to surgery (> 2 days), and preoperative DM were independent risk factors for postoperative ischemic ONFH (p < 0.05). Conclusion. The incidence of postoperative ischemic ONFH can be prevented by effectively controlling the following factors: age, BMI, PWB after surgery, and preoperative DM.